Pendampingan Penetatapan Kriteria Ketuntasan Minimal (KKM) Guru-guru Penjas se Kecamatan Siak Hulu Kabupaten Kampar - Zulrafli, Zulrafli; Kamarudin, Kamarudin; Mildawati, Roza; Elfina. S, Yetti; Gianti, Lisma; Mustakin, M. (Universitas Pahlawan Tuanku Tambusai, 2026)
Community Service Activities aim to improve teachers' ability in determining Minimum Completion which is a must for teachers before the school year begins for Physical Education Teachers in Siak Hulu District, Kampar Regency, for mentoring activities to determine Minimum Completion Criteria for Subjects, before the activity a Pretest and posttest were held after the mentoring activity. From the results of the mentoring activities, there was a positive impact, there was an increase in knowledge and understanding of Physical Education teachers in Siak Hulu District, and enthusiasm to participate in mentoring activities and were able to determine Minimum Completion Criteria which is an obligation for teachers to determine KKM at the beginning of the school year.